The correlation between sex and additive on blood biochemistry, and gut morphometric of broiler - Gallusia Marhaneny Nur Isty; Danung Nur Adli (Jurnal Nutrisi Ternak Tropis, 2022)
The correlation between sex and additive on blood biochemistry, and gut morphometric of broiler was investigated. First experiment were day-old-chicks of Ross 308 placed among control and experimental. The first experiment were used 56 Ross 308 broiler with aged 35 days including 28 males and 28 females as control, and 28 males and 28 females supplemented with or without probiotics. The second experiment were used nonlinear models of Gompertz models to predict between sex and probiotic effect on the growth performance. The data analyses were uses two-way of variance between probiotic and sex (male-female). At the end experiment (35 aged d) thus probiotic and sex were significant difference (p > 0.05) on live weight (g), glucose (mg/dL), and villus height (µm). Data were statistically analyses using of SAS University version 4.0 red hat (64-bit). To sum up, the interaction between group × sex was significant for body weight (g), villus height (µm) and trends reduce amount of glucose (mg/dL) of broiler and non-linear models were effective to comparison between in vivo and predicted models